ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MENGGUNAKAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT SMA MUHAMMADIYAH 1 PURWOKERTO - Desy Puspitasari; Sari Muliawanti; Gunawan Gunawan; Sairan Sairan (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
The purpose of this study is describing the mathematical problem solving ability using the TGT (Teams Games Tournament) learning model for the students of SMA Muhammadiyah 1 Purwokerto. This study uses qualitative research methods using the Miles and Huberman model which includes data reduction, data display, and conclusion (verification/conclusion drawing). The subjects of this study are students of X IPA 1 SMA Muhammadiyah 1 Purwokerto. By using purposive sampling technique, the students of  X IPA 1 were in three groups: the group of low achieving students, the group of medium achieving students, and the group of high achieving students. In each group, three students were selected to become respondents and then analyzed. Data collection methods in this study use questionnaire, tests, interviews, and documentation. From the results of this study, obtained: 1) the students with low achievement have a poor problem-solving ability, 2) the students with medium achievement have a good problem-solving ability, 3) the students with high achievement have great problem-solving skills.